em ENEM por

1 Resposta

0 votos

Hi there! I'd love to help you out.

First, we need to assign variables to our missing numbers. Let's say our first even number is x:

x = 1st even number

Now, we want to skip the odd number after our even number and use the next consecutive number. This means we need to add 2 to our first even number:

x + 2 = 2nd even number

Now we know their sum is 54. This means when we add them up, we get 54:

1st even number + 2nd even number = 54

Now we can substitute in our variables and solve:

x + x + 2 = 54

2x + 2 = 54

-2 -2

2x = 52

x = 26

So, our first even number is 26 and our second is 28. I hope this explanation was thorough and answered all of your questions. If you have any additional questions please don't hesitate to reach out. Learn on! :)